PENERAPAN LAYANAN E-GOVERNMENT DALAM PERWUJUDAN GOOD GOVERNANCE DI PEMERINTAH KOTA MALANG - Riski Febria Nurita (University of Merdeka Malang, 2016)
Implementation of E-Government in Indonesia and that has been achieved to date, the implementation strategy and E-Government concepts that inevitably require improvements on all sides. The delay in E-Government in development will only make this country away from the ideals of reform, improve the quality of public services to the whole society and ultimately can offend the welfare of society. Implementation of information and communication technology in government and development has become a demand, sooner or later in the era of globalization and regional autonomy that has led to a spirit of openness and empowerment of community potential, the emergence of public expectations of community needs. excellent service and speed Implementation of E-Government in Indonesia, especially in Malang City and the results that have been achieved to date and obstacles that hinder the implementation so that inevitably implementation strategy and E-Government concepts need improvement on all sides should be done as a motivation to build better. The E-Government’s delay in development will only keep the country away from reform ideas, improve the quality of public services to the rest of society and ultimately improve welfare.